COMPARATIVE ANALYSIS OF NATIONAL AND FOREIGN EXPERIENCES ON THE EXAMPLE OF THE CONSTITUTIONAL AND LEGAL BASIS OF ECOLOGICAL - Mallayev Normamat Ramazanovich (International Journal of Innovations in Engineering Research and Technology, 2021)
The Constitution sets out the main provisions of Uzbekistan’s environmental development strategy, requirements for environmental and environmental safety of the population, and this political and legal document defines the most important and basic rules for the protection of the environment and use of natural resources in our country. There are separate chapters and articles in the constitutions of the countries of the world, as well as many normative and legal acts in this regard.